Electrifying California fleets: Investigating light-duty vehicle purchase decisions. (March 2022) - Sugihara, Claire; Hardman, Scott
Highlights: Fleet purchasing differs significantly between electric and conventional vehicles. Fleets are electrifying primarily due to external factors. Sustainability and environmental considerations are the top reasons for electrifying. Fleets are electrifying but continue to face many barriers. Abstract: This paper uses results from interviews conducted with 23 fleet managers across California in 2019 to investigate fleet adoption of light duty Plug-in Electric Vehicles (PEVs). The interviews examined how fleet managers make vehicle purchase decisions and explored the motivations and barriers for the adoption of PEVs. The results are framed in the context of Self-Determination Theory which categorizes the level to which actions are taken based on internal and external motivators. Results show that conventional vehicle purchases are mostly motivated by internalized extrinsic motivators while PEV purchase decisions are mostly motivated by external extrinsic motivators, such as requirements to meet sustainability goals. While most fleets had adopted at least one PEV, there are still barriers to widespread electrification, including a lack of time and resources available to evaluate PEVs, issues with employee buy-in, a lack of total cost of ownership considerations, and infrastructure challenges. The results provide a greater understanding of fleet PEV purchasing, how PEVs align with existing purchase considerations, and how stakeholders could facilitate increased electric vehicle adoption in fleets.